2019
DOI: 10.3390/plants8070193
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Phytochemicals from Mercurialis spp. Used in Traditional Spanish Medicine

Abstract: Plants from the genus Mercurialis have a long history of use as herbal remedies in traditional Spanish medicine. The growing interest in the conservation of knowledge related to biodiversity has encouraged us to review the bioactive phytochemicals from the four most widespread Mercurialis species in the Iberian Peninsula (M. annua L., M. ambigua L., M. perennis L., and M. tomentosa L.). First, the medicinal uses of these four species throughout Spain were compiled, and then a bibliographical search on their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 54 publications
2
17
0
1
Order By: Relevance
“…Furthermore, plants of the genus Mercurialis spp . were widely used in Spain to different aims depending on the species of Mercurialis ( M. annua, M. ambigua, M. perennis, M. tomentosa): It can be used as an anti-hypertensive, laxative, abortive, anti-hyperglycemic, anti-arthrosis, hepatoprotective or anticolagogue [ 168 ]. In the 18th century, thanks to “Systema Naturae” (1735) and “Species Planetarium”, from Carolus Linnaeus, the botanical classification and the identification of thousands plants with specific characteristics began.…”
Section: Plant Extracts and Their Role In Nutraceutical Supplementmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, plants of the genus Mercurialis spp . were widely used in Spain to different aims depending on the species of Mercurialis ( M. annua, M. ambigua, M. perennis, M. tomentosa): It can be used as an anti-hypertensive, laxative, abortive, anti-hyperglycemic, anti-arthrosis, hepatoprotective or anticolagogue [ 168 ]. In the 18th century, thanks to “Systema Naturae” (1735) and “Species Planetarium”, from Carolus Linnaeus, the botanical classification and the identification of thousands plants with specific characteristics began.…”
Section: Plant Extracts and Their Role In Nutraceutical Supplementmentioning
confidence: 99%
“…In addition, flavonoids, oleuropein, ω-3 fatty acids, alkaloids and lycopene are natural compounds found in several plants, which can be useful in the prevention and management of CVDs as has been observed in many studies. The beneficial effects of all these natural compounds are mainly linked to their antioxidant, anti-inflammatory, antiplatelet, anti-hypercholesterolemic, anti-hypertensive actions, and to their ability to modulate High Density Lipoprotein (HDL)/Low Density Lipoprotein (LDL) ratio, protecting the endothelial function [ 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 ]. All these characteristics suggest that natural compounds could potentially be beneficial in counteracting the main risk factors and early pathological features of CVDs contributing to cardiac recovery.…”
Section: Plant Extracts and Their Role In Nutraceutical Supplementmentioning
confidence: 99%
“…were attributed to the flavonoids rutin and narcissin, respectively. Its anti-inflammatory activity was attributed to scopoletin, kaempferol, squalene, and cycloartenol [ 12 ].…”
Section: Preserving Ethnobotanical Knowledge and Plant Biodiversitmentioning
confidence: 99%
“…In addition, the plant was used to treat obstinate constipation and circumscribed inflammation in the intestines and stomach. It is useful against water retention and bladder infections [ 3 ]. It has diuretic properties, which increase urine production.…”
Section: Introductionmentioning
confidence: 99%
“…Biological activities research revealed an insecticide and larvicide robust potential in Mercurialis perennis L. and subsequently in M. annua [4]. Blanco-Salas et al (2019) [3] stated that the genus Mercurialis possesses antidiabetic and antihypertensive attributes due to the affluence of its aerial parts in flavonoids rutin and narcissin. Furthermore, this species was used in traditional pharmacopoeia against hair loss in Tunisia.…”
Section: Introductionmentioning
confidence: 99%